Deep cover [videorecording (DVD)] - Fishburne, Laurence, III, 1961-; Goldblum, Jeff, 1952-; Dillard, Victoria, 1969-; Sierra, Gregory; Williams, Clarence, III, 1939-2021 (Criterion collection, 2021)
"Film noir hits the mean streets of 1990s Los Angeles in this stylish and subversive underworld odyssey from veteran actor-director Bill Duke. Laurence Fishburne stars as Russell Stevens, a police officer who goes undercover as 'John Hull,' the partner of a dangerously ambitious cocaine trafficker (Jeff Goldblum), in order to bring down a powerful Latin American drug ring operating in LA. But the further Stevens descends into this ruthless world of money, violence, and power, the more disillusioned he becomes--and the harder it is to make out the line between right and wrong, crime and justice. Steeped in shadowy, neon-soaked atmosphere and featuring Dr. Dre's debut solo single, Deep Cover is an unsung gem of the nineties' Black cinemal explosion that delivers a riveting character study and sleek action thrills alongside a furious moral indictment of America and the devastating failures of the war on drugs"--Container.